The Netherlandic presence in Ontario : pillars, class and Dutch ethnicity - Schryer, Frans J. (Wilfrid Laurier University Press, 1998)
Annotation Schryer's central argument is that ethnic groups are as much modern "myths" as they are integral components of a socially constructed reality. Focusing on the large cohort of immigrants from the Netherlands and the former Dutch East Indies who arrived in Canada between 1947 and 1960, Schryer shows how the Dutch, despite a loss of ethnic identity and a high level of linguistic assimilation, replicated many aspects of their homeland. While illustrating and illuminating the diversity among immigrants sharing a common national origin, Schryer keeps sight of what is common among them. In doing so, he shows how deeply ingrained habits were modified in a Canadian context, resulting in both continuities and discontinuities. The result is a variegated image reflecting a multidimensional reality.
Keywords: Dutch -- Ontario.; Immigrants -- Ontario.; Dutch Canadians -- Ontario.; Néerlandais -- Ontario.; Canadiens d'origine néerlandaise -- Ontario.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Dutch; Immigrants; Ontario; e-books.; Livres numériques.